A novel FFQ for Brazilian adults based on the Nova classification system: development, reproducibility and validation - Evelyn Oliveira da Silva Frade; Kamila Tiemann Gabe; Caroline dos Santos Costa; Daniela Neri; Euridice Martínez-Steele; Fernanda Rauber; Josiane Steluti; Renata Bertazzi Levy; Maria Laura da Costa Louzada (Public Health Nutrition)
Abstract